A new species of Trachusa Panzer, 1804 (Megachilidae: Anthidiini) from southern Africa, with notes on the subgeneric classification and a key to the Afrotropical species - Kasparek, Max (Zootaxa, 2018)
Only a single species of the genus Trachusa Panzer, 1804 is currenlty known from southern Africa: Trachusa aquiphila (Strand, 1912). A second species is described here from Namibia: Trachusa namibiensis sp. n., with habitus similar to T. aquiphila, but distinguished by morphological characters and colour features. The new species combines features of the subgenera Trachusa (Paraanthidium Friese) and Trachusa (Massanthidium Pasteels), therefore the latter is here regarded as a junior synonym of Paraanthidium, and all three species which have been assigned to subgenus Massanthidium are here transferred to Trachusa (Paraanthidium). Trachusa (Paraanthidium) and Trachusa (Congotrachusa) are now the only subgenera occurring in sub-Saharan Africa. Trachusa namibiensis sp. n. seems not to be rare and was found sympatrically with T. aquiphila. It is polylectic and was found on the wing in autumn (March).